Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Distinguishing climate change worry from state climate anxiety across 32 countries: implications for subjective wellbeing - Eun Hee Lee; Charles Adedayo Ogunbode; Sibele Aquino; Navjot Bhullar; Mai Albzour; Rahkman Ardi; Arin H. Ayanian; Aydin Bayad; Laura Martinez Buelvas; Razieh Chegeni; JohnBosco Chika Chukwuorji; Rouven Doran; et al. (Journal of Environmental Studies and Sciences, 2026)
The concepts of “climate change worry” and “climate change anxiety” are often used interchangeably in climate research, but they may reflect distinct emotional responses to climate change, which could potentially have different implications for public mental health. This research brief aims to empirically examine the differences between these two constructs by comparing their associations with key indicators of subjective wellbeing. Using survey data from 32 countries ( N = 12,246), we compared how strongly climate change worry and state climate anxiety were each associated with subjective wellbeing, as measured by the WHO-5 Wellbeing Index and life satisfaction. State climate anxiety showed stronger associations with both WHO-5 Wellbeing Index and life satisfaction than climate change worry. This underscores the importance of treating the two as distinct emotional responses, each with different implications for public wellbeing. These insights are especially relevant for policymakers and climate communicators, who must carefully consider the emotional tone of climate messaging to foster constructive engagement while safeguarding the psychological wellbeing of the public.

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Post-seismic recovery and performance of high-rise RC buildings in diverse earthquake scenarios: a resilience-based approach - Moustafa Moufid Kassem; Fadzli Mohamed Nazri; H’ng Chee Yin; Salmia Beddu (Bulletin of Earthquake Engineering, 2025)

Genetic basis and role of exotic accessions in cultivated cotton fiber quality improvement - Ankush Sharma; Mingrui Xu; Deepak Vitrakoti; Jinesh D. Patel; Peng W. Chee; Andrew H. Paterson (Theoretical and Applied Genetics, 2025)
Key message Exotic Gossypium accessions still harbor QTL‑validated alleles that, combined with CRISPR pyramiding and genomic selection, can break the entrenched fiber length–strength trade‑off. Abstract Cotton’s four independent domestications twice in diploids and twice in allotetraploids offer a natural experiment in fiber improvement. Synthesizing three decades of data, we chart how polyploidy, selection and modern breeding have repeatedly reshaped the Gossypium genome. More than 15,000 quantitative trait locus (QTL) and genome wide association mapping studies (GWAS) hits converge on a handful of chromosomal “hotspots”; new MAGIC, NAM, NIL and long-read resources now narrow these peaks to < 200 kb, resolving causal genes such as GhHOX3, GhZF14 and GhMYB7 . Multi-omics evidence links auxin, ethylene, gibberellin, brassinosteroid and strigolactone signaling to HDZIP IV, MYB, bHLH/HLH and ERF networks that drive fiber initiation, extreme cell elongation and cellulose deposition. Population genomics shows that ~ 40% of favorable fiber alleles are fixed in elite Gossypium hirsutum , yet wild diploids and landraces still harbor variants that could break the length strength trade-off. We propose a three-step roadmap genomic selection, CRISPR gene pyramiding and accelerated introgression to expand cotton’s genetic base and deliver fibers suited to sustainable textile demands.

Genetic dissection of lint percentage and seed cotton yield in exotic x elite upland cotton crosses using population-specific and joint population analysis - Hrithik Mangla; Min Liu; Deepak Vitrakoti; Tariq Shehzad; Rahul Chandnani; Sayan Das; Jason G. Wallace; John L. Snider; Don C. Jones; Peng W. Chee; Andrew H. Paterson (Euphytica, 2025)
Limited genetic diversity for fiber quality and yield traits in the improved gene pool for Upland cotton motivates the exploration of exotic materials. In the present study, we carried out QTL mapping for 2 fiber yield components in five BC 1 F 2 and one F 3 resembling intermated population(s) involving 5 ‘converted’ exotic lines of Upland cotton and an elite cultivar “DES56,” as a common parent in all populations. The results indicated a higher frequency of dominant QTLs than additive QTLs. However, the prevalence of negative heterotic effects shows few opportunities to utilize these exotic lines for hybrid production. Most of the dominant QTLs were overdominant. In addition, all additive QTLs for lint percentage indicated the DES56 allele to be superior. These results suggest that selection practices need to be carried out in the later generations along with the implementation of precise marker-assisted selection to avoid the undesirable heterotic effects of these regions and reduce the linkage drag from undesirable alleles in the exotic segments. Moreover, the population-specific analysis and joint analysis showed the inflation of QTL parameters with a decrease in sample size, indicating the importance of larger sample sizes in mapping populations. Overall, the potential for using these exotic race stocks for hybrid production targeting yield components is limited.

Modelling climatic variable impacts on ground-level ozone in Malaysia using backward trajectory and Generative Additive Models - F. P. Chee; M. C.-G. Ooi; Y. J. Wong; J. Sentian; J. Dayou; M. T. Latif; J. H.-W. Chang (International Journal of Environmental Science and Technology, 2025)

Distinct N-cycling microbial communities contribute to microtopographic variation in soil N2O emissions from denitrification - Alexander H. Krichels; Robert A. Sanford; Joanne C. Chee-Sanford; Lynn Connor; Rachel Van Allen; Angela D. Kent; Wendy H. Yang (Soil Biology and Biochemistry, 2025)

Development and evaluation of a loop-mediated isothermal amplification (LAMP) method for Candida glabrata detection - H. Yahaya; Y. K. Cheah; H. Y. Chee; L. T. L. Than (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Elucidating the Correlation of Lignocellulosic Compositions and Physicochemical Alterations in Oil Palm (Elaeis guineensis) Biomass on Enzymatic Saccharification Yield - Tannimalay Hemashini; Chee Keong Lee; Choon Fu Goh; Ying Ying Tye; Maya Ismayati; Yin Ying H’ng; Cheu Peng Leh (BioEnergy Research, 2024)

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

An analysis of lncRNAs related to fiber quality and the discovery of their target genes in a Gossypium hirsutum line with Gossypium mustelinum introgression - Baohua Wang; Meijun Ji; Hui Fang; Haijing Gu; Teame Gereziher Mehari; Jinlei Han; Wenxiang Feng; Xuehan Huo; Jingxia Zhang; Yu Chen; Jun Zhang; Allah Ditta; et al. (Theoretical and Applied Genetics, 2024)

Optimisation and environmental impact analysis of green dry mix mortar paving block incorporating high volume recycled waste glass and ground granulated blast furnace slag - Jerome Song Yeo; Suhana Koting; Chiu Chuen Onn; Mohammed K. H. Radwan; Chee Ban Cheah; Kim Hung Mo (Environmental Science and Pollution Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Non-clinical Pharmacology of YTX-7739: a Clinical Stage Stearoyl-CoA Desaturase Inhibitor Being Developed for Parkinson’s Disease - Daniel F. Tardiff; Matthew Lucas; Iwona Wrona; Belle Chang; Chee Yeun Chung; Bertrand Le Bourdonnec; Kenneth J. Rhodes; Robert H. Scannevin (Molecular Neurobiology, 2022)
Summary Stearoyl-CoA desaturase (SCD) is a potential therapeutic target for Parkinson’s and related neurodegenerative diseases. SCD inhibition ameliorates neuronal toxicity caused by aberrant α-synuclein, a lipid-binding protein implicated in Parkinson’s disease. Its inhibition depletes monounsaturated fatty acids, which may modulate α-synuclein conformations and membrane interactions. Herein, we characterize the pharmacokinetic and pharmacodynamic properties of YTX-7739, a clinical-stage SCD inhibitor. Administration of YTX-7739 to rats and monkeys for 15 days caused a dose-dependent increase in YTX-7739 concentrations that were well-tolerated and associated with concentration-dependent reductions in the fatty acid desaturation index (FADI), the ratio of monounsaturated to saturated fatty acids. An approximate 50% maximal reduction in the carbon-16 desaturation index was observed in the brain, with comparable responses in the plasma and skin. A study with a diet supplemented in SCD products indicates that changes in brain C16 desaturation were due to local SCD inhibition, rather than to changes in systemic fatty acids that reach the brain. Assessment of pharmacodynamic response onset and reversibility kinetics indicated that approximately 7 days of dosing were required to achieve maximal responses, which persisted for at least 2 days after cessation of dosing. YTX-7739 thus achieved sufficient concentrations in the brain to inhibit SCD and produce pharmacodynamic responses that were well-tolerated in rats and monkeys. These results provide a framework for evaluating YTX-7739 pharmacology clinically as a disease-modifying therapy to treat synucleinopathies.

Economic study on biohydrogen production from liquid pineapple waste - Syaza I. Ahmad; Roslina Rashid; Zanariah Hashim; Chew Chee Meng; Chong Kar Lun; Den Muhammad Hamdi Jumaatuden; Norhidayah Ahmad Yasin; Ashella Jati; Mimi H. Hassim (Clean Technologies and Environmental Policy, 2022)

Beyond denitrification: The role of microbial diversity in controlling nitrous oxide reduction and soil nitrous oxide emissions - Jun Shan; Robert A. Sanford; Joanne Chee‐Sanford; Sean K. Ooi; Frank E. Löffler; Konstantinos T. Konstantinidis; Wendy H. Yang (Global Change Biology, 2021)
Many biotic and abiotic processes contribute to nitrous oxide (N 2 O) production in the biosphere, but N 2 O consumption in the environment has heretofore been attributed primarily to canonical denitrifying microorganisms. The nosZ genes encoding the N 2 O reductase enzyme, NosZ, responsible for N 2 O reduction to dinitrogen are now known to include two distinct groups: the well‐studied Clade I which denitrifiers typically possess, and the novel Clade II possessed by diverse groups of microorganisms, most of which are non‐denitrifiers. Clade II N 2 O reducers could play an important, previously unrecognized role in controlling N 2 O emissions for several reasons, including: (1) the consumption of N 2 O produced by processes other than denitrification, (2) hypothesized non‐respiratory functions of NosZ as an electron sink or for N 2 O detoxification, (3) possible differing enzyme kinetics of Clade II NosZ compared to Clade I NosZ, and (4) greater nosZ gene abundance for Clade II compared to Clade I in soils of many ecosystems. Despite the potential ecological significance of Clade II NosZ, a census of 800 peer‐reviewed original research articles discussing nosZ and published from 2013 to 2019 showed that the percentage of articles evaluating or mentioning Clade II nosZ increased from 5% in 2013 to only 22% in 2019. The census revealed that the slowly spreading awareness of Clade II nosZ may result in part from disciplinary silos, with the percentage of nosZ articles mentioning Clade II nosZ ranging from 0% in Agriculture and Agronomy journals to 32% in Multidisciplinary Sciences journals. In addition, inconsistent nomenclature for Clade I nosZ and Clade II nosZ , with 17 different terminologies used in the literature, may have created confusion about the two distinct groups of N 2 O reducers. We provide recommendations to accelerate advances in understanding the role of the diversity of N 2 O reducers in regulating soil N 2 O emissions.

Whole genome sequencing analysis of multidrug-resistant tuberculosis in Singapore, 2006–2018 - Cynthia B. E. Chee; Leo K. Y. Lim; Rick T. H. Ong; Li Hwei Sng; Li Yang Hsu; Vernon J. M. Lee; Yee Tang Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Microbiome and environment explain the absence of correlations between consumers and their diet in Bornean microsnails - Kasper P. Hendriks; Karen Bisschop; Hylke H. Kortenbosch; James C. Kavanagh; Anaïs E. A. Larue; Phung Chee‐Chean; Dries Bonte; Elza J. Duijm; Joana Falcão Salles; Alex L. Pigot; Francisco J. Richter Mendoza; Menno Schilthuizen; et al. (Ecology, 2021)
Classical ecological theory posits that species partition resources such that each species occupies a unique resource niche. In general, the availability of more resources allows more species to co‐occur. Thus, a strong relationship between communities of consumers and their resources is expected. However, correlations may be influenced by other layers in the food web, or by the environment. Here we show, by studying the relationship between communities of consumers (land snails) and individual diets (from seed plants), that there is in fact no direct, or at most a weak but negative, relationship. However, we found that the diversity of the individual microbiome positively correlates with both consumer community diversity and individual diet diversity in three target species. Moreover, these correlations were affected by various environmental variables, such as anthropogenic activity, habitat island size, and a possibly important nutrient source, guano runoff from nearby caves. Our results suggest that the microbiome and the environment explain the absence of correlations between diet and consumer community diversity. Hence, we advocate that microbiome inventories are routinely added to any community dietary analysis, which our study shows can be done with relatively little extra effort. Our approach presents the tools to quickly obtain an overview of the relationships between consumers and their resources. We anticipate our approach to be useful for ecologists and environmentalists studying different communities in a local food web.

An Overview of the Expert Consensus on the Prevention and Treatment of Gaming Disorder in China (2019 Edition) - Yu-Tao Xiang; Yu Jin; Ling Zhang; Lu Li; Gabor S. Ungvari; Chee H. Ng; Min Zhao; Wei Hao (Neuroscience Bulletin, 2020)

S-Adenosylmethionine (SAMe) monotherapy for depression: an 8-week double-blind, randomised, controlled trial - Jerome Sarris; Jenifer Murphy; Con Stough; David Mischoulon; Chad Bousman; Patricia MacDonald; Laura Adams; Sonia Nazareth; Georgina Oliver; Lachlan Cribb; Karen Savage; Ranjit Menon; et al. (Psychopharmacology, 2020)

Simulation analysis of the future surface ozone in Malaysian region under representative concentration pathways (RCPs) emission scenarios - S. S. K. Kong; J. Sentian; M. T. Chuang; M. C. G. Ooi; F. P. Chee; J. H. W. Chang (International Journal of Environmental Science and Technology, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Comparative genetic variation of fiber quality traits in reciprocal advanced backcross populations - Rahul Chandnani; Zhengsheng Zhang; Jinesh D. Patel; Jeevan Adhikari; Sameer Khanal; Daohua He; Nino Brown; Peng W. Chee; Andrew H. Paterson (Euphytica, 2017)

Betanodavirus : Dissection of the viral life cycle - C‐F Low; B Syarul Nataqain; H‐Y Chee; M Z H Rozaini; M Najiah (Journal of Fish Diseases, 2017)
Progressive research has been recently made in dissecting the molecular biology of Betanodavirus life cycle, the causative pathogen of viral encephalopathy and retinopathy in economic important marine fish species. Establishment of betanodavirus infectious clone allows the manipulation of virus genome for functional genomic study, which elucidates the biological event of the viral life cycle at molecular level. The betanodavirus strategizes its replication by expressing anti‐apoptosis/antinecrotic proteins to maintain the cell viability during early infection. Subsequently utilizes and controls the biological machinery of the infected cells for viral genome replication. Towards the late phase of infection, mass production of capsid protein for virion assembly induces the activation of host apoptosis pathway. It eventually leads to the cell lysis and death, which the lysis of cell contributes to the accomplishment of viral shedding that completes a viral life cycle. The recent efforts to dissect the entire betanodavirus life cycle are currently reviewed.

Segregation distortion and genome-wide digenic interactions affect transmission of introgressed chromatin from wild cotton species - Rahul Chandnani; Baohua Wang; Xavier Draye; Lisa K. Rainville; Susan Auckland; Zhimin Zhuang; Edward L. Lubbers; O. Lloyd May; Peng W. Chee; Andrew H. Paterson (Theoretical and Applied Genetics, 2017)

Streptococcus agalactiae outbreaks in cultured golden pomfret, Trachinotus blochii (Lacépède), in Singapore - S M Chong; W K Wong; W Y Lee; Z B Tan; Y H Tay; X H Teo; L D Chee; C J Fernandez (Journal of Fish Diseases, 2017)

Fine mapping and candidate gene analysis of qFL-chr1, a fiber length QTL in cotton - Peng Xu; Jin Gao; Zhibin Cao; Peng W. Chee; Qi Guo; Zhenzhen Xu; Andrew H. Paterson; Xianggui Zhang; Xinlian Shen (Theoretical and Applied Genetics, 2017)

QTL analysis of cotton fiber length in advanced backcross populations derived from a cross between Gossypium hirsutum and G. mustelinum - Baohua Wang; Xavier Draye; Zhimin Zhuang; Zhengsheng Zhang; Min Liu; Edward L. Lubbers; Don Jones; O. Lloyd May; Andrew H. Paterson; Peng W. Chee (Theoretical and Applied Genetics, 2017)

Identification of immune response‐related genes and signalling pathways in spleen of Vibrio parahaemolyticus ‐infected Epinephelus fuscoguttatus (Forskal) by next‐generation sequencing - C‐F Low; N S Mariana; A Maha; H‐Y Chee; M Y Fatimah (Journal of Fish Diseases, 2016)

Non‐immune‐related genes and signalling pathways in spleen of Vibrio parahaemolyticus ‐infected Epinephelus fuscoguttatus (Forskal) - C‐F Low; N S Mariana; A Maha; H‐Y Chee; M Y Fatimah (Journal of Fish Diseases, 2015)

Antimycobacterial activity and in silico study of highly functionalised dispiropyrrolidines - Ang Chee Wei; Mohamed Ashraf Ali; Yeong Keng Yoon; Sy Bing Choi; Hasnah Osman; Vijay H. Masand; Tan Soo Choon (Medicinal Chemistry Research, 2015)

Experimental infection of brown‐marbled grouper, E pinephelus fuscoguttatus (Forskal), with V ibrio parahaemolyticus identifies parvalbumin beta‐2 subunit I, alpha‐2‐macroglobulin, nattectin and immunoglobulin light chain, differentially expressed in resistant grouper - C‐F Low; M Nor Shamsudin; M Abdullah; H‐Y Chee; M Aliyu‐Paiko (Journal of Fish Diseases, 2015)
The mechanisms through which brown‐marbled grouper accomplishes resistance to infection, particularly against Vibrios , are not yet fully understood. In this study, brown‐marbled grouper fingerlings were experimentally infected with Vibrio parahaemolyticus, to identify disease resistance grouper, and the serum proteome profiles were compared between resistant and susceptible candidates, via two‐dimensional gel electrophoresis (2‐ DE ). The results showed that putative parvalbumin beta‐2 subunit I, alpha‐2‐macroglobulin, nattectin and immunoglobulin light chain proteins were among proteins that significantly overexpressed in the resistant fish as compared to the susceptible group of fish, whereas apolipoprotein E and immunoglobulin light chain proteins were observed to be differentially overexpressed in the susceptible fish. Further analysis by peptide sequencing revealed that the immunoglobulin light chain proteins identified in the resistant and susceptible groups differed in amino acid composition. Taken together, the results demonstrated for the first time that putative parvalbumin beta‐2 subunit I, alpha‐2‐macroglobulin, nattectin and immunoglobulin light chain are among important proteins participating to effect disease resistance mechanism in fish and were overexpressed to function collectively to resist V. parahaemolyticus infection. Most of these molecules are mediators of immune response.

Putative apolipoprotein A‐I, natural killer cell enhancement factor and lysozyme g are involved in the early immune response of brown‐marbled grouper, Epinephelus fuscoguttatus, Forskal, to Vibrio alginolyticus - C‐F Low; M N Shamsudin; H‐Y Chee; M Aliyu‐Paiko; E S Idrus (Journal of Fish Diseases, 2014)
The gram‐negative bacterium, Vibrio alginolyticus , has frequently been identified as the pathogen responsible for the infectious disease called vibriosis. This disease is one of the major challenges facing brown‐marbled grouper aquaculture, causing fish farmers globally to suffer substantial economic losses. The objective of this study was to investigate the proteins involved in the immune response of brown‐marbled grouper fingerlings during their initial encounter with pathogenic organisms. To achieve this objective, a challenge experiment was performed, in which healthy brown‐marbled grouper fingerlings were divided into two groups. Fish in the treated group were subjected to intraperitoneal injection with an infectious dose of V. alginolyticus suspended in phosphate‐buffered saline ( PBS ), and those in the control group were injected with an equal volume of PBS . Blood samples were collected from a replicate number of fish from both groups at 4 h post‐challenge and analysed for immune response‐related serum proteins via two‐dimensional gel electrophoresis. The results showed that 14 protein spots were altered between the treated and control groups; these protein spots were further analysed to determine the identity of each protein via MALDI ‐ TOF / TOF . Among the altered proteins, three were clearly overexpressed in the treated group compared with the control; these were identified as putative apolipoprotein A‐I, natural killer cell enhancement factor and lysozyme g. Based on these results, these three highly expressed proteins participate in immune response‐related reactions during the initial exposure (4 h) of brown‐marbled grouper fingerling to V. alginolyticus infection.

Systematic approach for conceptual design of an integrated biorefinery with uncertainties - Mei Chee Tang; Markus W. S. Chin; King Ming Lim; Yee San Mun; Rex T. L. Ng; Douglas H. S. Tay; Denny K. S. Ng (Clean Technologies and Environmental Policy, 2013)

The pathology of ‘scale drop syndrome’ in Asian seabass, Lates calcarifer Bloch, a first description - S Gibson‐Kueh; D Chee; J Chen; Y H Wang; S Tay; L N Leong; M L Ng; J B Jones; P K Nicholls; H W Ferguson (Journal of Fish Diseases, 2012)
This is the first pathological description of ‘scale drop syndrome’ (SDS) in Asian seabass, Lates calcarifer Bloch. Cumulative mortality was estimated at 40–50%. The vasculitis in all major organs including the skin and associated tissue necrosis was distinctive. The dermis overlying scale beds was often necrotic and associated with scale loss. Necrosis of splenic ellipsoids, renal glomeruli and choroid rete glands of eye were further hallmarks of a disease with systemic vascular involvement. The brain was not spared vascular damage, and the resulting multifocal encephalomalacia probably accounts for the spiral swimming behaviour in some affected fish. Other lesions included accentuated hepatic lobulation and gastric gland necrosis. Nuclear chromatin margination and karyolysis in hepatocytes, renal tubular epithelium and gastric and intestinal epithelium suggest specific targeting of cells. Basophilic cytoplasmic inclusions were present in spleen, kidney, liver, heart and choroid rete, but they were not prominent. Using transmission electron microscopy, two morphological forms of virions were observed: single‐ and double‐enveloped hexagonal virions. Based on size and morphology, these virions resemble iridovirus or herpesvirus. The cause of SDS is unknown, but the pathological changes, especially the vasculitis, suggest an infectious aetiology, possibly viral.

QTL alleles for improved fiber quality from a wild Hawaiian cotton, Gossypium tomentosum - Zhengsheng Zhang; Junkang Rong; Vijay N. Waghmare; Peng W. Chee; O. Lloyd May; Robert J. Wright; John R. Gannaway; Andrew H. Paterson (Theoretical and Applied Genetics, 2011)

Identification of QTL genes for BMD variation using both linkage and gene-based association approaches - Gloria Hoi-Yee Li; Ching-Lung Cheung; Su-Mei Xiao; Kam-Shing Lau; Yi Gao; Cora H. Bow; Qing-Yang Huang; Pak-Chung Sham; Annie Wai-Chee Kung (Human Genetics, 2011)

Sequencing and Utilization of the Gossypium Genomes - Andrew H. Paterson; Jun-kang Rong; Alan R. Gingle; Peng W. Chee; Elizabeth S. Dennis; Danny Llewellyn; Leon S. Dure; Candace Haigler; Gerald O. Myers; Daniel G. Peterson; Mehboob ur Rahman; Yusuf Zafar; et al. (Tropical Plant Biology, 2010)

Quantitative T-cell interferon-gamma responses to Mycobacterium tuberculosis-specific antigens in active and latent tuberculosis - C. B. E. Chee; T. M. S. Barkham; K. W. KhinMar; S. H. Gan; Y. T. Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Resistance exercise effects on blood glutathione status and plasma protein carbonyls: influence of partial vascular occlusion - A. H. Goldfarb; R. S. Garten; P. D. M. Chee; C. Cho; G. V. Reeves; D. B. Hollander; C. Thomas; K. S. Aboudehen; M. Francois; R. R. Kraemer (European Journal of Applied Physiology, 2008)

Decreased adhesiveness, resistance to anoikis and suppression of GRP94 are integral to the survival of circulating tumor cells in prostate cancer - Edward W. Howard; Steve C. L. Leung; H. F. Yuen; Chee Wai Chua; Davy T. Lee; K. W. Chan; Xianghong Wang; Yong Chuan Wong (Clinical & Experimental Metastasis, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genetic mapping and comparative analysis of seven mutants related to seed fiber development in cotton - Junkang Rong; Gary J. Pierce; Vijay N. Waghmare; Carl J. Rogers; Aparna Desai; Peng W. Chee; O. Lloyd May; John R. Gannaway; Jonathan F. Wendel; Thea A. Wilkins; Andrew H. Paterson (Theoretical and Applied Genetics, 2005)

Molecular dissection of interspecific variation between Gossypium hirsutum and G. barbadense (cotton) by a backcross-self approach: II. Fiber fineness - Xavier Draye; Peng Chee; Chun-Xiao Jiang; Laura Decanini; Terrye A. Delmonte; Robert Bredhauer; C. Wayne Smith; Andrew H. Paterson (Theoretical and Applied Genetics, 2005)

Molecular dissection of interspecific variation between Gossypium hirsutum and Gossypium barbadense (cotton) by a backcross-self approach: I. Fiber elongation - Peng Chee; Xavier Draye; Chun-Xiao Jiang; Laura Decanini; Terrye A. Delmonte; Robert Bredhauer; C. Wayne Smith; Andrew H. Paterson (Theoretical and Applied Genetics, 2005)

Molecular dissection of phenotypic variation between Gossypium hirsutum and Gossypium barbadense (cotton) by a backcross-self approach: III. Fiber length - Peng W. Chee; Xavier Draye; Chun-Xiao Jiang; Laura Decanini; Terrie A. Delmonte; Robert Bredhauer; C. Wayne Smith; Andrew H. Paterson (Theoretical and Applied Genetics, 2005)

Fluorescent in situ mapping of the murine deleted in split hand/split foot 1 (dss1) gene to Chromosome 6 - Michael A. Crackower; Henny H. Q. Heng; Xiaomei Shi; Stephen W. Scherer; Lap-Chee Tsuil (Mammalian Genome, 1997)

Microwave-Assisted Solvent Extraction of Air Particulates for the Determination of PAHs - K. K. Chee; M. K. Wong; H. K. Lee (Environmental Monitoring and Assessment, 1997)

Optimization of the Microwave-Assisted Solvent Extraction of Petroleum Hydrocarbons in Marine Sediment and Soil - K. K. Chee; M. K. Wong; H. K. Lee (Environmental Monitoring and Assessment, 1997)

Sequence and Phylogenetic Analysis of the Cytoplasmic Inclusion Protein Gene of Zucchini Yellow Mosaic Potyvirus: Its Role in Classification of the Potyviridae - CHEE-GIOK Chng; KIAN-CHUNG Lee; PARVESH H Mahtani; SEK-MAN Wong (Virus Genes, 1997)